Smoking Cessation Practices in Kuwaiti General Dental Clinics - Khalaf, Mai (Med Princ Pract, 2013)
OBJECTIVES: This study aimed to determine the degree of involvement of general dental practitioners working in primary health care centers of the Ministry of Health (MOH) of Kuwait in tobacco cessation activities. SUBJECTS AND METHODS: A survey questionnaire composed of 48 structured multiple choice questions aimed at assessing practitioner knowledge, attitudes, perceived expectations, confidence, and perceived barriers preventing them from performing these activities was distributed to 150 general dentists working in MOH dental clinics. RESULTS: One hundred forty-five dentists responded to the survey questionnaire. Twelve (12%) surveyed practitioners always or almost always incorporated overall tobacco cessation activities into their practice. Forty-one (3%) of the respondents felt that they had excellent cessation knowledge. One (1%) felt barriers prohibited their performance of cessation activities. One hundred (76%) participants strongly agreed that there was an expectation for them to perform cessation activities in their clinics. Fourteen (10%) respondents felt very confident about their cessation counseling skills. CONCLUSIONS: Findings showed that smoking cessation practices are not performed on a routine basis in MOH dental clinics. Practitioner knowledge and confidence showed the most significant association with the performance of cessation activities.